THE RESISTANCE CULTURE IN LATIN AMERICAN STUDENTS: 1810—2010 - Biagini, Hugo E. (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
This paper deals with Latin American youth and its special protagonism in three different stages: South American Independence, Cordoba’s reformist movement and the alterglobalisation phenomenon of today. Adopting dissident attitudes and against authoritative principles, those students struggled for modern teaching, scientific advances and the opening of university to people and society.